New findings about the spatial and temporal use of the Eastern Atlantic Ocean by large juvenile loggerhead turtles. Issue 4 (24th January 2016) - Varo‐Cruz, Nuria; Bermejo, Juan A.; Calabuig, Pascual; Cejudo, Daniel; Godley, Brendan J.; López‐Jurado, Luis F.; Pikesley, Stephen K.; Witt, Matthew J.; Hawkes, Lucy A.
Abstract: Aims: Effective conservation of threatened or endangered species requires a robust understanding of their spatio‐temporal distribution. Although a huge amount is known about the movements of Atlantic adult sea turtles, much less is known about juvenile turtles, and much of the life history model is therefore inferred. We set out to describe the spatio‐temporal distribution of juvenile loggerheads turtles found around the Canary Islands. Location: Eastern North Atlantic Ocean. Methods: Between 1999 and 2012, we satellite‐tracked 24 healthy large juvenile loggerhead turtles (mean straight carapace length = 47.4 cm, range = 34.6–54.5 cm) captured in the waters around the Canary Islands. We describe their regional distribution, identify high‐use areas and create a model for habitat suitability using minimum convex polygons, density rasters and ensemble ecological niche modelling, integrated with physical and biological environmental data. Results: Turtles used a huge oceanic area (2.5 million km 2 ) with particularly high usage around the Canary Islands, Spain, Portugal, Morocco and Western Sahara. In spring and summer, turtles generally moved further north towards the Iberian Peninsula. Ecological niche modelling identified sea surface temperature as the most important contributory variable to the habitat models. We also recorded three juvenile turtles making westward migrations away from the eastern Atlantic Ocean, presumably back towards their original natal beaches near sexual maturity. Main conclusions: The results of the present study provide insight into a significant knowledge gap on the spatio‐temporal distribution of large juvenile loggerhead turtles in the eastern Atlantic Ocean. The data highlight that turtles occupy a vast open oceanic area, which hampers the ability of static conservation approaches to afford effective protection. However, ensemble ecological niche modelling highlights key suitable habitat for juvenile loggerhead turtles, which could be used in dynamic conservation protection.